Impact of ISBAR Communication Training on Interpersonal Communication and Teamwork of Residents in General Practice Standardized Training - Chen, Min; Yin, Jianhao; Jia, Rui; Zhang, Hao; Yan, Rong; Zhang, Yong (Technium Social Sciences Journal, 2020)
Interpersonal communication and teamwork is one of the training objectives of standardized training for residents. The ISBAR (Identify, Situation, Background, Assessment, Request) communication training model can effectively improve physicians’ clinical communication skills and teamwork ability. Our research aims to explore the impact of the ISBAR communication training on the interpersonal communication and teamwork of residents in general practice standardized training. A total of 92 general practitioners (GP) who participated in the Standardized Residency Training in the First Affiliated Hospital of Xi’an Jiaotong University in September 2018 were randomly recruited and divided into observation group?n=46? and control group?n=46? using simple random grouping method. GP in the observation group was trained by the ISBAR communication training model, whereas GP in the control group was trained by the traditional clinical education model. Six different scales were used to assess the interpersonal communication ability and teamwork ability of the two groups at different time points. After two weeks of training?the scores of interpersonal communication ability and teamwork ability in the observation group were higher than those in the control group?P<0.05?. ISBAR communication training model may significantly improve the interpersonal communication skills and teamwork ability of residents in general practice standardized training.